Cultivating Proactive Career Behavior: The Role of Career Adaptability and Job Embeddedness - Peng, Peng; Song, Yu; Yu, Guangtao (Frontiers in Psychology, 2021)
Scholars have widely acknowledged that proactive career behavior is essential for individuals to proactively build their careers, as well as facilitate positive career outcomes. However, there are still many questions about how to activate proactive career behavior. In the current study, we consider whether, how and when regulatory focus of individuals would evoke their proactive career behavior. Based on career construction theory, we utilized the career adaptability framework to develop and test the mediating effect of individual regulatory focus on proactive career behavior through career adaptability. Moreover, we further proposed that job embeddedness plays a contingency role in moderating the extent to which regulatory focus contributes to proactive career behavior with the mediation of career adaptability differently and uniquely. Using a sample of 247 participants and collecting data in three waves, we found that the promotion focus of employees positively influences their proactive career behavior through the mediation of career adaptability. Furthermore, the indirect effect of promotion focus on proactive career behavior via career adaptability was moderated by the dichotomy of job embeddedness of individuals respectively and differently. Specifically, the positive relationship between promotion focus and proactive career behavior via the mediation of career adaptability was strengthened by the on-the-job embeddedness of employees, whereas the relationship was weakened by their off-the-job embeddedness. The overall findings broaden our understanding in terms of the underlying mechanism of proactive career behavior, suggesting that the promotion focus of individuals fosters proactive career behavior via career adaptability, and on-the-job and off-the-job embeddedness as contingency factors alter the effect of career adaptability.